Entre désolation et consolation : Lire les Pensées de Pascal aujourd’hui - Hall Bjørnstad (Les Dossiers du GRIHL)
This article explores the conceptual space opened by the preposition “between” in its title – “between desolation and consolation” – by assessing the complexity and stakes of this space not only for Pascal himself, his voices in the text and for the reader as constructed by the text, but also for the text itself qua material object as it reaches us today. In doing so, the article pursues a peculiar parallelism between this reader and the text itself: on both sides, there emerges a constitutive loss and a primordial desolation. In this context, the “reopening” of the Pensées emphasized already in the title of this volume could therefore be understood, in a more dramatic and violent sense, as that of a wound: confronting yet again an alleged primordial desolation, whether that of the reader or that of the text, acutely aware that the loss cannot be repaired, at least not in this world. In other words, reopening the Pensées, while resisting a too rapid, too easy or too superficial consolation.